2014
DOI: 10.1177/0022034514556709
|View full text |Cite
|
Sign up to set email alerts
|

Iron Binding Modulates Candidacidal Properties of Salivary Histatin 5

Abstract: Salivary protein histatin 5 (Hst 5) is fungicidal toward Candida albicans, the causative agent of oropharyngeal candidiasis. However, its activity in saliva is compromised by salivary protease-mediated degradation and interaction with salivary salts. Hst 5 has also been shown to bind various metals in saliva-namely, Zn, Cu, and Ni. Surprisingly, interactions of Hst 5 with Fe have not been studied, although iron is one of the most abundant metals present in saliva. Using circular dichroism, we show that Hst 5 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 33 publications
2
60
0
4
Order By: Relevance
“…For example, the binding of Ca 2+ by MSP at low pH potentiates the activity of the peptide by alleviating inhibitory mechanisms that are mediated by the ion [37] and metal ion binding by histidine residues appears able to promote microbial death through depletion of these ions for a number of antimicrobial molecules, such as histatins [141,143,155]. In contrast, the binding of metal ions appears to potentiate the activity of some antimicrobial molecules reviewed here by promoting their capacity to form peptide–membrane or peptide–peptide salt bridges and thereby disrupt microbial membranes, as proposed for kappacins [197] and DCD-1(L) respectively [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the binding of Ca 2+ by MSP at low pH potentiates the activity of the peptide by alleviating inhibitory mechanisms that are mediated by the ion [37] and metal ion binding by histidine residues appears able to promote microbial death through depletion of these ions for a number of antimicrobial molecules, such as histatins [141,143,155]. In contrast, the binding of metal ions appears to potentiate the activity of some antimicrobial molecules reviewed here by promoting their capacity to form peptide–membrane or peptide–peptide salt bridges and thereby disrupt microbial membranes, as proposed for kappacins [197] and DCD-1(L) respectively [50].…”
Section: Discussionmentioning
confidence: 99%
“…Low pH appears able to enhance the antifungal activity of hst-1, hst-3 [154] and hst-5 [45], which, for example, enhances the positive charge carried by hst-5 and facilitates its translocation into fungal cells to attack intracellular targets [45]. However, a detailed description of the antifungal activity of these peptides is lacking and a number of mechanisms have been proposed [141,143,144,145,146], such as complex formation with iron to interfere with the cellular metabolism of the metal in fungi, such as C. albicans [155]. Studies on human lactoferrin, which is a multifunctional iron-binding protein [156] found that low pH enhanced the ability of sub-lethal levels of the protein to kill C. albicans , through multiple mechanisms, including dissipation of the proton motive force (PMF) across the CM of the organism [47].…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%
“…Metal-binding properties of Hist-5 have been proposed for nearly two decades, 15, 2122 and its metal-binding interactions with Cu(II), Ni(II), Zn(II) and Fe(III) have been investigated in vitro. 2126 Metal binding has been observed to modify the conformation and biological activity of Hist-5.…”
mentioning
confidence: 99%
“…22 At least one study showed that supplemental Zn(II) improved the bactericidal activity of Hist-5, 28 while other studies showed no effect of Zn on Hist-5 candidacidal activity. 22 On the other hand, Fe supplementation was observed to decrease the in vitro candidacidal activity of Hist-5, and Hist-5 itself caused a decrease in expression levels of iron uptake genes in C. albicans . 22 …”
mentioning
confidence: 99%
“…In saliva, iron is a cofactor of lactoferrin, an important salivary protein with antibacterial activity that strongly binds to two iron atoms and salivary bicarbonate, thus limiting the presence of iron in bacterial cells and making saliva strongly bacteriostatic [8,9,21]. When associated with histatin, it also has antifungal activity [22].…”
Section: Discussionmentioning
confidence: 99%